AKUNTABILITAS IMPLEMENTOR KEBIJAKAN PEMASYARAKATAN DI RUTAN KELAS I PEKANBARU - Popi Anggraini; Hasim As’ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Correctional is an activity to provide guidance to Prisoners based on the system, institution and method of coaching which is the final part of the criminal justice system in the criminal justice system. Detention Center is a place for prisoners to carry out rehabilitation or a place for prisoners to serve their sentences. Accountability is the responsibility of the management or trustee to the trustee for the management of the resources entrusted to him either vertically or horizontally. The one who carries out the mandate or becomes the executor is the implementor. The purpose of this research is to find out how the Implementors of Correctional Policy Implementors are accountable and to find out what are the inhibiting factors in the Accountability of the Correctional Policy Implementors. The theory used is the theory of Janet V Denhardt and Robert B. Denhardt, that Public Service Accountability must be carried out based on the principles: Serving citizens, Meeting all public needs, Citizenship values above entrepreneurial values, Thinking strategically and acting democratically, It must be understood that accountability in the administration of public services cannot be simplified, Serve rather than direct, Assess humanity not only productivity. This study uses a qualitative research type with a descriptive approach and the required data, both primary and secondary data, were obtained by means of observation, interviews and documentation, for further selection of informants was carried out by purposive sampling and snowball sampling. The results of this study indicate that: first, the Accountability of Correctional Policy Implementors at the Class I Rutan Pekanbaru is not yet accountable because there are still violations committed by the Rutan and have not fulfilled the seven principles/indicators that the authors use such as serving citizens, fulfilling all public needs, and values. citizenship above the entrepreneurial value. Second, the inhibiting factors are overcapacity, the place in charge of prisoners who are far away and the behavior of the implementor.  Keywords : Accountability, Implementor, Correctional policy